ESTIMATES OF THE SECOND DISSOCIATION CONSTANT OF H2S FROM THE SURFACE SULFIDATION OF CRYSTALLINE SULFUR - Migdisov A.A.; Williams-Jones A.E.; Lakshtanov L.Z.; Alekhin Y.V. (My University, 2002)
The adsorption of hydrogen sulfide (ΓH2S) and protons (ΓH+) on the surface of crystalline sulfur was investigated experimentally in H2S-bearing solutions at temperatures of 25, 50, and 70°C, NaCl concentrations of 0.1 and 0.5 mol/dm−3 and log CH+ values in the range −2.3 to −5. At all temperatures, the dominant process on the surface of the sulfur was deprotonation, and the average values of ΓH2S were very close to the highest values determined for ΓH+. This finding, combined with the lack of detectable proton adsorption in H2S-free solutions, suggests that proton adsorption/desorption on the surface of sulfur occurs through formation of ≡ S − H2S complexes in the presence of H2S.We propose that this complexation represents sulfidation of the sulfur surface, a process analogous to hydroxylation of oxide surfaces, and that the sulfidation can be described by the reaction: ≡ S + H2S = ≡SSH20 β° The deprotonation of the ≡ SH° complex occurs via the reaction: ≡ SSH20 = ≡SSH− + H+ β− Values of 2.9, 2.8, and 2.9 (± 0.23) were obtained for −log β− at 25, 50, and 70°C, respectively. These data were employed to estimate the second dissociation constant for hydrogen sulfide in aqueous solutions using the extrapolation method proposed by Schoonen and Barnes (1988) and yielded corresponding values for the constant of 17.4 ± 0.3, 15.7, and 14.5, respectively. The value for 25°C is in very good agreement with the experimentally determined values of Giggenbach (1971) at 17 ± 0.1; Meyer et al. (1983) at 17 ± 1; Licht and Manassen (1987) at 17.6 ± 0.3; and Licht et al. (1990) at 17.1 ± 0.3.